A Novel Trajectory for a Transpedicular Approach in the Treatment of a Highly Downward-Migrated Lumbar Herniation with a Full Endoscopic Technique - Jiang, Yi; Zuo, Rujun; Yuan, Shuai; Li, Jian; Liu, Chang; Zhang, Jiexun; Ma, Ming (Frontiers in Surgery, 2022)
Background To evaluate the clinical outcome of full endoscopic discectomy using a novel trajectory via a transpedicular approach. Method Thirty-five patients were enrolled in this retrospective study between July 2014 and October 2019 in the Beijing Haidian Hospital. All patients were treated with full-endoscopic lumbar discectomy via a transpedicular approach with an oblique trajectory. The imaging parameters, including pedicle height and angle of trajectory, were recorded. The preoperative and postoperative clinical data were collected for statistical analysis. Results All patients underwent successful surgery without severe complications. We compared the visual analogue scale and Oswestry disability index scores before and after surgery. The differences were statistically significant (p < 0.05). According to the modified Macnab criteria, the good-to-excellent rate was 85.7% at the last follow-up. The average angles of trajectory in the sagittal and coronal planes were 34.5° ± 2.9° and 47.1° ± 5.0°, respectively. Conclusion The new trajectory of the transpedicular approach with a full endoscopic technique for an extremely downward-migrated disc herniation showed excellent results in a small sample study. A precise surgical plan is required, comprising measurements of the pedicle height and angle of the bone tunnel.